Older adults with cancer in the city of São Paulo: what factors determine the place of death? - Adna Kelly Ferreira Leite; Karina Braga Ribeiro (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE Investigate factors associated with death at home among older adults who died of cancer in a large city. METHODS This is a descriptive study, including all cancer deaths (ICD C00-C97) occurring between 2006 and 2012, among residents of the city of São Paulo, 60 years of age or older. The data source was the Mortality Information System, and the proportion of deaths was calculated according to place of occurrence, gender, age, race/skin color, education, marital status, cancer type, hospital bed availability, and year of death. The chi-squared test was used to examine the associations between the place of death and sociodemographic and clinical variables. Logistic regression was used to identify factors associated with home death. Crude and adjusted odds ratios and the corresponding 95% confidence intervals were estimated. RESULTS Most of the deaths occurred in hospitals (88.2%). There was a significant association between the place of death and the following variables: gender, race/skin color, education, age, marital status, cancer type, hospital bed availability, and year of death. In the multivariate analysis, all variables, except the availability of hospital beds, remained as independent predictors of death at home. CONCLUSIONS There was a predominance of hospital deaths, with an increase in frequency in the period. Female gender, higher education, married or widowed status, and black race were associated with a decreased risk of death at home, while increasing age, Asian race, and solid neoplasms were associated with higher risk of dying at home.